The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jrs.5264
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time metabolite monitoring of glucose‐fed Clostridium acetobutylicum fermentations using Raman assisted metabolomics

Abstract: Data obtained from in situ Raman spectroscopy probes and high‐performance liquid chromatography (HPLC) analysis were applied together with chemometrics to build partial least squares models of metabolite concentrations for the industrially relevant organism Clostridium acetobutylicum. Models were built for predominant products (acetic acid, butyric acid, and butanol) of C. acetobutylicum cultures grown on glucose as a substrate. The partial least squares models were then applied to a 3‐day C. acetobutylicum cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Clostridium sp. was initially propagated on CGM under anaerobic conditions described previously 28 , 40 . 500 µL of potato-glucose suspension (PGM) spore stock was heat-shocked at 80 °C for 10 min, then re-suspended in 150 mL CGM enriched with 0.5% of the respective carbohydrate (i.e., glucose, galacturonate, gluconate, or mixtures two or three of these substrates).…”
Section: Methodsmentioning
confidence: 99%
“…Clostridium sp. was initially propagated on CGM under anaerobic conditions described previously 28 , 40 . 500 µL of potato-glucose suspension (PGM) spore stock was heat-shocked at 80 °C for 10 min, then re-suspended in 150 mL CGM enriched with 0.5% of the respective carbohydrate (i.e., glucose, galacturonate, gluconate, or mixtures two or three of these substrates).…”
Section: Methodsmentioning
confidence: 99%
“…They used data obtained from in situ Raman spectroscopy probes and HPLC analysis, together with chemometrics, to build partial least square models of metabolite concentrations for the industrially relevant organism C. acetobutylicum . They concluded that predictive models based upon Raman spectral data are promising tools for characterization of synthetic organisms, guiding process control, and facilitating optimization of culture conditions …”
Section: Biosciencesmentioning
confidence: 99%
“…Fermentation monitoring is a pivotal tool for bioprocess optimization and control. Assessing the state of the process via high‐resolution time‐course analysis allows detailed characterization during process development, as well as rapid detection and correction of any possible deviations from desired process specifications during product manufacturing, ensuring the quality of the end product (Svendsen et al, 2015; Zu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, these vibrational spectroscopy technologies have certain limitations, the main one being that the spectra that they generate are very convoluted with many overlapping signals. This results in the need to use chemometric mathematical models such as partial least squares (PLS) regression to break down the different signals contributed by the different compounds in the mixture (do Nascimento et al, 2017; Li et al, 2018; Marison et al, 2012; Rodrigues et al, 2018; Stuart, 2005; Zu et al, 2017). These models require significant time and resources to build and are usually not transferable, that is, they are only applicable to the configuration used to build them (bioreactor, medium composition, strain, temperature, pH, etc.)…”
Section: Introductionmentioning
confidence: 99%